WiTNNess: An international natural history study of infantile‐onset TNNT1 myopathy - Kevin A. Strauss; Vincent J. Carson; Emilienne Bolettieri; Mariah Everett; Ashton Bollinger; Lauren E. Bowser; Keturah Beiler; Millie Young; Simon Edvardson; Nitay Fraenkel; Adele D'Amico; Enrico Bertini; et al. (Annals of Clinical and Translational Neurology, 2023)
ABSTRACT Objective We created WiTNNess as a hybrid prospective/cross‐sectional observational study to simulate a clinical trial for infantile‐onset TNNT1 myopathy. Our aims were to identify populations for future trial enrollment, rehearse outcome assessments, specify endpoints, and refine trial logistics. Methods Eligible participants had biallelic pathogenic variants of TNNT1 and infantile‐onset proximal weakness without confounding conditions. The primary endpoint was ventilator‐free survival. “Thriving” was a secondary endpoint defined as the ability to swallow and grow normally without non‐oral feeding support. Endpoints of gross motor function included independent sitting and standing as defined by the Word Health Organization, a novel TNNT1 abbreviated motor score, and video mapping of limb movement. We recorded adverse events, concomitant medications, and indices of organ function to serve as comparators of safety in future trials. Results Sixteen children were enrolled in the aggregate cohort (6 prospective, 10 cross‐sectional; median census age 2.3 years, range 0.5–13.8). Median ventilator‐free survival was 20.2 months and probability of death or permanent mechanical ventilation was 100% by age 60 months. All six children (100%) in the prospective arm failed to thrive by age 12 months. Only 2 of 16 (13%) children in the aggregate cohort sat independently and none stood alone. Novel exploratory motor assessments also proved informative. Laboratory and imaging data suggest that primary manifestations of TNNT1 deficiency are restricted to skeletal muscle. Interpretation WiTNNess allowed us to streamline and economize the collection of historical control data without compromising scientific rigor, and thereby establish a sound operational framework for future clinical trials.